Efficacy and Safety of Subthreshold Micropulse Yellow Laser for Persistent Diabetic Macular Edema After Vitrectomy: A Pilot Study - Bonfiglio, Vincenza; Rejdak, Robert; Nowomiejska, Katarzyna; Zweifel, Sandrine Anne; Justus Wiest, Maximilian Robert; Romano, Giovanni Luca; Bucolo, Claudio; Gozzo, Lucia; Castellino, Niccolò; Patane, Clara; Pizzo, Corrado; Reibaldi, Michele; et al. (Frontiers in Pharmacology, 2022)
Aim: To examine the effect of subthreshold micropulse yellow laser (SMYL) on best-corrected visual acuity (BCVA), central macular thickness (CMT), and optical coherence tomography angiography (OCT-A) changes in eyes with persistent diabetic macular edema (DME) after pars plana vitrectomy (PPV) for tractional DME (TDME). Patients and Methods: In a comparative study, 95 eyes of 95 consecutive patients with persistent DME were prospectively enrolled. The SMYL group (54 eyes) was treated with SMYL 6 months after PPV, while the control group (41 eyes) was followed up without treatment. BCVA and CMT by OCT were analyzed at baseline and 3 and 6 months. Additionally, parameters such as the vessel density (VD) in the superficial capillary plexus (SCP) and deep capillary plexus (DCP), respectively, and the area of the foveal avascular zone (FAZ) were also evaluated on OCT-A. Results: There were no significant differences between both groups in demographic data. In the SMYL group, mean BCVA was significantly increased [F(2,106) = 17.25; p < 0.001; ηp2 = 0.246] from 51.54 ± 13.81 ETDRS letters at baseline to 57.81 ± 12.82 ETDRS letters at 3 months (p < 0.001) and 57.83 ± 13.95 EDTRS letters at 6 months (p < 0.001), respectively. In comparison to the control group, BCVA values were statistically significantly higher in the SMYL group at 3 and 6 months, respectively. Mean CMT significantly decreased [F(2,106) = 30.98; p < 0.001; ηp2 = 0.368] from the baseline value 410.59 ± 129.91 μm to 323.50 ± 89.66 μm at 3 months (p < 0.001) and to 283.39 ± 73.45 μm at 6 months (p < 0.001). CMT values were significantly lower in the SMYL group (p < 0.001), especially at 6 months follow-up time (p < 0.001) compared with the control group. Parafoveal VD in the SCP and DCP was significantly higher in the SMYL group in comparison to the control group, respectively, at 3-month (SCP p < 0.001; DCP p < 0.001) and 6-month follow-up (SCP p < 0.001; DCP p < 0.001). FAZ area was also significantly smaller in the SMYL group at 6-month follow-up (p = 0.001). There were no adverse SMYL treatment effects. Conclusion: SMYL therapy may be a safe and effective treatment option in eyes with persistent macular edema following PPV for TDME.